Comparison of Early Maladaptive Schemas, Lifestyle, Resilience and Happiness in Iranian Women Working in Toronto and Tehran with Emphasis on the Role of Immigration - Kiani, Anahita; Kordmirza Nikoozadeh, Ezatollah; Hosseini Almadani, Seyed Ali (International Journal of Applied Behavioral Sciences, 2020)
Introduction: One of the most important developments in immigration in recent decades is the increasing involvement of women in the immigration process and the increase in women’s independent immigration, which is called the feminization of immigration. This study aimed to comparing Iranian women working in Toronto and Tehran in lifestyle, early maladaptive schemas, resilience, and happiness. Methods: The present study was a causal-comparative study. The statistical population included all Iranian women working in Tehran and Iranian women immigrating to – Toronto, Canada. Using the convenient sampling method, 89 Iranian women working in Toronto and 93 Iranian women working in Tehran were selected (Out of the total number of questionnaires, 11 questionnaires from the group of immigrants and 7 questionnaires from the group of non-immigrants were excluded due to being distorted). Data collection tool included Young Schemas Questionnaire (YSQ-SF), Adler Basic Scales for Interpersonal Success - Adult Edition (BASIS-A), Connor and Davidson Resilience Scale, and Happiness / Depression Inventory. Results: The results of MANOVA showed that there is a significant difference between the mean scores of some lifestyle components (p<0.05), a number of early maladaptive schemas (p<0.05), happiness components (p<0.05), and resilience of immigrant and non-immigrant women (p<0.05). Conclusion: Accordingly, immigration in Iranian women can be a factor for changes in various aspects of psychology such as resilience, happiness and lifestyle.